1999
DOI: 10.1073/pnas.96.18.10146
|View full text |Cite
|
Sign up to set email alerts
|

A tubular endosomal fraction from rat liver: Biochemical evidence of receptor sorting by default

Abstract: We previously have isolated an endosomal fraction from rat liver, termed receptor-recycling compartment (RRC), which is highly enriched in recycling receptors and in the transcytotic polymeric Ig receptor (pIgR). We now have analyzed the RRC fraction by immunoisolation and found that no uniquely transcytotic elements were present, because recycling receptors and the pIgR were coisolated on the same elements. In addition, RRC was very rich in proteins previously shown to be associated with recycling endosomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 37 publications
(45 reference statements)
4
47
1
Order By: Relevance
“…This compartment is enriched in basolaterally endocytosed IgA and depleted of TfR with respect to the CE. Ultrastuctural studies in MDCK cells (5) and cell fractionation of rat liver suggested that the ARE and tubular CE probably represent a single compartment that might be divided into different domains (5,36). This was largely based on the observation that whenever TfR and IgA colocalized, their relative concentrations appeared to be the same.…”
Section: Discussionmentioning
confidence: 98%
“…This compartment is enriched in basolaterally endocytosed IgA and depleted of TfR with respect to the CE. Ultrastuctural studies in MDCK cells (5) and cell fractionation of rat liver suggested that the ARE and tubular CE probably represent a single compartment that might be divided into different domains (5,36). This was largely based on the observation that whenever TfR and IgA colocalized, their relative concentrations appeared to be the same.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to the uncoupling of mammalian LDL from LDLR in sorting endosomes, HDLp remains attached to its receptor despite the decrease in lumenal pH. Endosome tubulation followed by iterative fractionation of membrane-anchored recycling receptors results in efficient receptor recycling by default (Dunn et al, 1989;Verges et al, 1999). Consequently, ligands that remain coupled to such receptors are recycled as well.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural studies in MDCK cells and cell fractionation of rat liver suggested that the ARE and tubular CE represent a single compartment that is subdivided into different domains Verges et al, 1999). By contrast, the non-overlapping or partially overlapping distribution of distinct SAC-associated markers, such as various Rab proteins, emphasized the subcompartmentalization of the SAC (van IJzendoorn and Hoekstra, 1999).…”
Section: The Subapical Compartment(s)mentioning
confidence: 99%